Patients Aged ≥55 Years With Stage T1-2N1M1 Differentiated Thyroid Cancer Should Be Downstaged in the Eighth Edition AJCC/TNM Cancer Staging System - Liu, Zeming; Chen, Sichao; Huang, Yihui; Hu, Di; Wang, Min; Wei, Wei; Zhang, Chao; Zeng, Wen; Guo, Liang (Frontiers in Oncology, 2019)
Objectives: Since the eighth edition of the American Joint Committee on Cancer tumor-node-metastasis (AJCC/TNM) cancer staging system introduced some significant changes, we investigated whether patients with stage T1-2N1M1 differentiated thyroid cancer (DTC) should be placed in stage IVB, with the goal of providing suggestions for improved survival prediction. Materials and Methods: We divided 30,234 DTC patients aged ≥55 years enrolled from the Surveillance, Epidemiology, and End Results (SEER) database into different stage groups based on the new stage system but in a more thorough manner. Univariate and multivariate Cox regression analyses were conducted to explore the clinicopathological factors associated with cancer-specific survival. Survival of different stage groups was assessed by mortality rates per 1,000 person-years, Cox proportional hazards regression analyses, and Kaplan-Meier analyses with log-rank tests and the propensity score matching method. Results: Univariate and multivariate analyses demonstrated that age at diagnosis, T stage, lymph node metastasis, distant metastasis, histological types, extrathyroidal extension, and radiation therapy were associated with cancer-specific survival. Patients with stage T1-2N1M1 had a lower cancer-specific mortality rate per 1,000 person-years (28.081, 95% confidence interval [CI]: 12.616–62.505) and all-cause mortality rate per 1,000 person-years (70.203, 95% CI: 42.323–116.448) than those with low-level stages such as stage T4aN1M0, stage IVA, and stage T1-2N0M1. Cox proportional hazards regression analyses suggested that patients with stage T4bN1M0 belonging to stage IVA (hazard ratio: 2.529, 95% CI: 1.018–6.278, p = 0.046) had a significantly higher risk of cancer-specific mortality than those with stage T1-2N1M1. Kaplan-Meier analyses with log-rank tests suggested that the cancer-specific survival curve of patients with stage T1-2N1M1 had a more modest decline than that of stage T4bN1M0 (p = 0.0125), and the cancer-specific survival curve and all-cause survival curve of patients with stage T1-2N1M1 were not different from those of stage T3N1M0, stage T4aN0M0, stage T4aN1M0, stage T4bN0M0, and stage T1-2N0M1 (all, p > 0.05). The analysis yielded similar results after propensity score matching for other clinicopathological characteristics. Conclusion: Patients aged ≥55 years with stage T1-2N1M1 DTC according to the eighth edition AJCC/TNM cancer staging system should be downstaged and those with stage T4bN1M0 upstaged accordingly.